2020
DOI: 10.1128/aac.00522-20
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Omadacycline, a New Tetracycline Analog, and Comparators against Clostridioides difficile

Abstract: Omadacycline is a potent aminomethylcycline with in vitro activity against Gram-positive, Gram-negative, and anaerobic bacteria. Preliminary data demonstrated that omadacycline has in vitro activity against Clostridioides difficile; however, large-scale in vitro studies have not been done. The purpose of this study was to assess the in vitro susceptibility of omadacycline and comparators on a large biobank of clinical C. difficile isolates. In vitro C. difficile susceptibility to omadacycline and comparators (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…The MIC 50 and MIC 90 of omadacycline reported from the present study are comparable with the results (MIC 50 , 0.25 mg/liter, and MIC 90 , 0.5 mg/liter) from a previous study that used the agar dilution method for MIC determination among 21 clinical isolates of C. difficile ( 8 ). In contrast, our results are higher than the MIC 50 (0.031 μg/ml) and MIC 90 (0.031 μg/ml) reported in a more recent study from Texas, USA ( 11 ). The ribotypes tested and, more importantly, the method (broth microdilution) employed for MIC determination in the study reported by Begum et al were different from the ribotypes and method in our study.…”
Section: Observationcontrasting
confidence: 92%
“…The MIC 50 and MIC 90 of omadacycline reported from the present study are comparable with the results (MIC 50 , 0.25 mg/liter, and MIC 90 , 0.5 mg/liter) from a previous study that used the agar dilution method for MIC determination among 21 clinical isolates of C. difficile ( 8 ). In contrast, our results are higher than the MIC 50 (0.031 μg/ml) and MIC 90 (0.031 μg/ml) reported in a more recent study from Texas, USA ( 11 ). The ribotypes tested and, more importantly, the method (broth microdilution) employed for MIC determination in the study reported by Begum et al were different from the ribotypes and method in our study.…”
Section: Observationcontrasting
confidence: 92%
“…In the Panel 4 study, omadacycline demonstrated potent in vitro activity, with a broth dilution MIC 50/90 value of 0.031/0.031 mg/L and MIC values ranging from 0.016 to 0.13 mg/L against 250 C. difficile isolates collected between 2015 and 2018 from 13 hospitals in the Houston, TX, region. 37 Omadacycline displayed equally potent activity among the 7 different ribotypes in this collection and regardless of CDI disease severity or vancomycin susceptibility. 37 In time-kill kinetic studies, bacterial killing was similar to (or more potent than) fidaxomicin, metronidazole, and vancomycin, with omadacycline demonstrating bactericidal effects by 24 hours (>3 log 10 colony-forming units [CFU]/mL killing).…”
Section: Resultsmentioning
confidence: 80%
“…A total of 14 studies of omadacycline and C. difficile were unanimously included covering in vitro activity, preclinical models, clinical trials, and health economics and outcomes research (HEOR); no case reports were found (Figure 1). [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]…”
Section: Methodsmentioning
confidence: 99%
“…C. difficile was strain typed using a PCR-based ribotyping method, as described elsewhere [ 14 ]. Minimum inhibitory concentrations were determined for ibezapolstat by broth microdilution in 0.1% sodium taurocholate brain heart infusion media [ 15 ].…”
Section: Methodsmentioning
confidence: 99%